On-farm conservation activities in Akole and Shahada, Maharashtra, India - Mittra, Sarika; Rana, Jai Chand (Bioversity International and International Center for Tropical Agriculture, 2025)
Progress on the on-farm conservation activities implemented at the project sites in Maharashtra, India under the Multifunctional Landscapes (MFL) Program. This report summarizes the activities that have been carried out in the Akole and Shahada clusters of Maharashtra, India as part of the HLO ‘OP 1.1.1. Bundles of robust and highly adapted solutions and innovations to enhance farm-level productivity, resilience and sustainability within landscapes’. The activities include on-farm trials of multiple crops using the tricot approach, establishment of on-farm conservation centers and capacity building that have been implemented with our local NGO partner BAIF Development Research Foundation.